Science of Information (Global Journal of Science Frontier Research, 2021)
Nature and character of information defy observable, positivistic, and reductionist science. Still, a science of information could be possible with logically woven ideas expressed in a common universal language in the third person's perspective connected with the physical science of matter, energy, space and time on the superficial hand, and the cognitive faculty on the deeper hand. With the thread left out by twentieth century's science the paper begins with a linguistic analysis of information, narrates its properties, mechanics, different geometrical states, and relates dark energy of cosmology with visible energy of cell biology with credible impacts on science, humanities, and consciousness studies.
Keywords: information mechanics; information states; information geometry